Annual summary of admiralty notices to mariners - amendments to sailing directions : correct to 25 December 2008 (week 52/08) (Admiralty Chart & Publications, 2009)
Contents : Part 1 Current editions of admiralty sailing directions and their latest supplements ; Part 2 Amendments in force